Role of honey bee on mustard (Brassica spp.) yield (Journal of Biodiversity Conservation and Bioresource Management, 2021)
The study was conducted in the field at Nagarpur, Tangail, Bangladesh, from November 2016 to February 2017 to find out the role of honey bees on mustard yield. Honey bee (Apis mellifera) was the main insect pollinator during mustard flowering season. Mustard seeds of variety Tori-7 were selected for this experiment. Three different treatments were used, viz. control, netting with honey bees and netting without honey bees. Honey bees helped mustard pollination, but decreased the flowering period (6 days) of the mustard plant. Honey bees assisted the pollination of mustard and increased the number of pod per plant (14%) as well as the number of seeds per pod (11%). Honey bees enhanced the pollination of mustard plant, and netting with honey bees increased the mean seed yield (15%) per plant of mustard, however, decreased the period of flowering stage of mustard. Mustard yield was considerably higher in honey bee foraging plots.J. Biodivers. Conserv. Bioresour. Manag. 2020, 6(1): 25-30